2004
DOI: 10.1111/j.1365-2982.2004.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clonidine and tricyclic antidepressants on gastric smooth muscle contractility

Abstract: To determine if and how clonidine and tricyclic antidepressants affect gastric contractility. Guinea pig fundic and antral circular muscle strips were studied in vitro. The effects of clonidine or amitriptyline added in graded concentrations on contractions to electric field stimulation (EFS), acetylcholine (ACh), and SP in the presence of N(epsilon)-nitro-l-arginine methyl ester (l-NAME) were studied. EFS produced frequency dependent contractions of fundic and antral muscle that were abolished by atropine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The role of sympathetic neuronal input in modulating gastric vagal cholinergic functions has been well studied and several investigators have reported that alpha-2 adrenoceptors are present presynaptically on cholinergic nerves [36]. Studies in fundus preparations from various species have shown that stimulation of alpha-2 adrenoceptors inhibits both the release of ACh and the neuronal-induced contractions [37,38]. Therefore, it is reasonable to believe that the effect of clonidine in WKY rats is at least partly mediated through stimulation of alpha-2 adrenoceptors located presynaptically on cholinergic myenteric neurons, resulting in reduced ACh release that normalizes the disturbed vagal cholinergic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The role of sympathetic neuronal input in modulating gastric vagal cholinergic functions has been well studied and several investigators have reported that alpha-2 adrenoceptors are present presynaptically on cholinergic nerves [36]. Studies in fundus preparations from various species have shown that stimulation of alpha-2 adrenoceptors inhibits both the release of ACh and the neuronal-induced contractions [37,38]. Therefore, it is reasonable to believe that the effect of clonidine in WKY rats is at least partly mediated through stimulation of alpha-2 adrenoceptors located presynaptically on cholinergic myenteric neurons, resulting in reduced ACh release that normalizes the disturbed vagal cholinergic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…James et al [16] observed that effects of tricyclic antidepressants on gastric smooth muscle contractility in guinea pig, and found that amitriptyline reduced contractions induced by ACh. Huang & Lau [17] reported that in the rat isolated trachea, amitriptyline produced a shift to the right of ACh concentration-contraction curve without affecting the maximum contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Largely mediated by anticholinergic activity, most studies with TCAs show a delayed transit 86,[159][160][161] or decreased muscle activity. 162,163 Reported effects on pain levels prompted investigations on visceral sensation with variable findings. Using balloon distension as a physiologically relevant stimulus, most studies found no or at best marginal effects on responses to esophageal, 164,165 gastric, 162 or rectal distension 166 in humans.…”
Section: Tcas In Ibdmentioning
confidence: 99%